Shear strength of compacted soils - Zhong, Yixuan (2018)
The aim of this Final Year Project is to study the shear strength of soil which are either statically compacted or dynamically compacted and to compare any differences arising from each compaction method. Dynamically compacted soil samples were compacted following the instruction of Modified Proctor Test. For statically compacted soil samples, a California Bearing Ratio (CBR) machine was utilised to compact the soil samples to the same dry density as on the modified Proctor compaction curve. The obtained data were subsequently analysed to investigate the impact of different compaction method to the soil properties.